Evidence of attenuation of intestinal ischemia–reperfusion injury following pre-treatment with methanolic extracts from Chromolena odorata in rats (2015)
Background: Chromolena odorata is a tropical species of flowering shrub in the family Asteraceae, leaves of it have been reported to be widely used as herbal remedy for the treatment of various ailments. It is particularly reported to be useful in the healing of wounds. Methods: We investigated the possibility of amelioration of intestinal ischemia–reperfusion (IR) injury in rats trea ted with methanolic extract of C. odorata (MECO). Wistar albino rats were divided randomly into five groups of six animals each as control, IR-treated, IR þ 200 mg/kg MECO, IR þ 400 mg/kg MECO, and IR þ 200 mg/kg vita min C. Pre-treatment with MECO or vitamin C was for 7 days. Results: The contents of hydrogen peroxide (H2O2) and malondialdehyde (MDA) were significantly reduced by MECO and vitamin C, while there were significant enhancements of the activities of superoxide dismutase (SOD), glutathione peroxidase (GPX), catalase (CAT), as well as the content of reduced glutathione (GSH) in pre-treated rats compared to IR-treated rats. Glutathione S-transferase (GST) activity was not significantly affected in all the groups. Histopathological examination of small intestinal mucosa revealed significant attenuation of intestinal pathology in animals pre-treated with MECO, while IR injury produced severe villi erosion, necrosis, and inflammatory cell infiltrations. Conclusions: The present study highlights the antioxi dant activities of MECO and its ability to inhibit inflammatory cell infiltration as mechanisms involved in its protection against IR injury in the intestine of rats, an effect that was largely comparable to that of vitamin C.